RESPON PERTUMBUHAN EKSPLAN ANGGREK BULAN (Phalaenopsis amabilis. L) TERHADAP PEMBERIAN NAPHTALENE ACETIC ACID (NAA) DAN AIR KELAPA SECARA IN VITRO - Noer Arif Hardi; Hasan Basri Jumin; Maizar (UIR Press, 2022)
This study was conducted in the biotechnology laboratory of the Faculty of Agriculture, Riau Islamic University, Pekanbaru. This study was conducted for five months from January to March 2017. The purpose of this study was to examine the effect of the growth response of an orchid butterfly plant on the interaction between NAA and coconut water using In-Vitro. This study used a Completely Randomized Design (RAL) factorial the RAL (Randomized ich consists of two factors. The first factor was NAA consisting of 4 levels, i.e 0, 0.1 ppm, 1.0 ppm, and 10,0 ppm, and the second factor was Coconut Water which also consisted of 4 levels, i.e 30%, 60%, and 90%. With 3 repetitions, the parameters observed: percentage of live explants (%), percentage of explants form shoots (%), number, percentage of explants that make up the root (%), explant form callus (%), shoot age (day), and the percentage of explant form plantlets (%). The last observational data were statistically analyzed and continued with BNJ advanced test at a 5% level. As a result, the interaction of NAA and coconut water affected the percentage of explant root and the percentage of explant form callus with the best concentration of 10 ppm NAA. The provision of coconut water had a significant effect on the number of shoots, the percentage of an explant from the roots shoot emergence, explant percentage forming plantlets on moth orchids with a concentration of 30% Coconut water/L media.